The clash of civilizations and the remaking of world order - Huntington, Samuel P. (New York Simon & Schuster, 2011)
The Clash of Civilizations and the Remaking of World Order explains how the population explosion in Muslim countries and the economic rise of East Asia are changing global politics. These developments challenge Western dominance, promote opposition to supposedly ?universal? Western ideals, and intensify intercivilization conflict over such issues as nuclear proliferation, immigration, human rights, and democracy. The Muslim population surge has led to many small wars throughout Eurasia, and the rise of China could lead to a global war of civilizations. Huntington offers a strategy for the West to preserve its unique culture and emphasizes the need for people everywhere to learn to coexist in a complex, multipolar, muliticivilizational world.
Includes bibliographical references and index.
Keywords: World politics --1989-